3D gait analysis, haemophilia joint health score, leg muscle laterality and biomarkers of joint damage: A cross‐sectional comparative assessment of haemophilic arthropathy. Issue 6 (3rd October 2020) - Putz, Peter; Durstberger, Sebastian; Kaufmann, Christina; Klinger, Meike; Plessl, Kerstin; Rejtö, Judit; Widhalm, Klaus; Male, Christoph; Pabinger, Ingrid
Abstract: Introduction: 3D gait analysis has been proposed as a reproducible and valid method to assess abnormal gait patterns and to monitor disease progression in patients with haemophilia (PWH). Aim: This study aimed at comparing Gait Deviation Index (GDI) between adult PWH and healthy controls, and at assessing the agreement between outcome measures of haemophilic arthropathy. Methods: Male PWH aged 18‐49 years (prespecified subgroups: 18‐25 vs 26‐49 years) on prophylactic replacement therapy, and male healthy age‐matched controls passed through a cross‐sectional assessment panel. Besides the 3D gait analysis derived GDI, secondary outcomes included kinematic, kinetic and spatio‐temporal gait parameters, the Haemophilia Joint Health Score (HJHS), electric impedance derived leg muscle laterality and inflammatory biomarkers. Results: Patients with haemophilia (n = 18) walked slower, in shorter steps and accordingly with less functional range of motion in the hips and ankles, as compared to healthy controls (n = 24). Overall, PWH did not differ significantly in GDI and specific gait parameters. PWH had a higher mean HJHS (18.8 vs 2.6, P  = .000) and leg muscle laterality (4.3% vs 1.5%, P  = .004). A subgroup analysis revealed progressed gait pathology in PWH aged 26‐49 years (not statistically significant). Leg muscle laterality was strongly correlated with HJHS ( r  = .76, P  = .000), whereas GDI just moderately ( r  = −.39, P  = .110). PWH had higher levels of the inflammatory markers CRP and IL‐6. Conclusion: Progressed gait pathology was found in PWH, mainly those aged 26‐49 years. Leg muscle laterality correlated strongly with HJHS and was identified as a promising tool for detecting progression and physiological consequences of haemophilic joint arthropathy.